Channel sharing utility function of power control game in cognitive femtocell network - Anggun Fitrian Isnawati; Risanuri Hidayat; Selo Sulistyo; I Wayan Mustika (IAES Indonesian Section, 2019)
The use of sharing channel simultaneously has become the trend in telecommunication technology particularly in network with distributed users as the allocation of frequency spectrum becomes more crowded. The proposed power control method in cognitive femtocell network is based on game theory (commonly known as power control game, PCG). This method uses utility function formula as the goal of game theory for power strategy in power update process. Utility function formula of Proposed PCG includes channel sharing factor that aimed to accommodate the system requirement of channel sharing. The result showed that the implementation of channel factor is inversely proportional to the signal to noise and interference ratio (SINR) and transmit power, but proportional to utility function. In comparison of user transmit power and SINR with two other methods, can also be conclude that Proposed PCG was able to achieve SINR of 5.49 dB and above the SINR target 5 dB, while the Thalabani (TB) and Koskie-Gajic (KG) were only able to achieve respective SINR of 4.87 dB and 4.98 dB. It can be concluded that the Proposed PCG was better in achieving the SINR target. It means that the quality of service in this system can be fulfilled properly.